INTENTION DETERMINANT OF POTENTIAL INDIVIDUAL INVESTORS IN DECISION MAKING OF SHARE INVESTMENT IN INDONESIA STOCK EXCHANGE - Sri Hermuningsih; Kusuma Chandra Kirana; Ratih Kusumawardhani (Program Studi Akuntansi Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2018)
Capital market is a vehicle that can mobilize long-term fundraising from the society to be channeled into productive sectors through the sale of stocks, bonds, mutual funds and derivatives. Investment decision-making is a process of selecting the best alternative from a number of alternatives available under the influence of complex situations, will be greatly influenced by the received information, the level of capability and knowledge of the investors about investment. Financial behavior aims to understand the behavior of investors in making investment decisions. The purpose of this study is to examine and obtain empirical evidence of potential individual investors’ determination in making decision of stock investment. This type of research is quantitative research with purposive sampling technique. The population used in this research is the students of the Faculty of Economics, University of Sarjanawiayata Tamansiswa Yogyakarta. The sample used is 50 UST students who want to be a share investor in Indonesia Stock Exchange. The methods of data collection use questionnaires and structured questions. Data analysis technique use Structural Equation Modeling. The results of this study noted that the quality of accounting information, subjective norms, perceptions of behavior control and risk perceptions do not systematically affect on the intention of prospective individual investors in decision-making stock investment in Indonesia Stock Exchange. Keywords: Intention, Investor. Indonesia Stock Exchange